Juridical Review of Child Drugs User in Indonesia - Imawan Sugiharto (International Journal of Science and Society, 2019)
Narcotics can endanger human life if misused and have very broad negative effects. This is indicated by the number of cases of drug users from year to year from various groups including children. Therefore, both the dealer and the user are charged with a very heavy article. This study aims to determine the dangers of narcotics abuse as well as a juridical review for underage offenders. The method used is the normative juridical method. From this research it is known that underage drug users are charged under Article 114 Paragraph (1) of the Law Number 35 of 2009 about Drugs.